Răspunsuri la întrebare
Răspuns de
1
o sa i iau pe bucati:
(r3+r6)^2=
3+2r18+6=
9+6r2
(r2-r3)^2=
2-2r6+3=
5-2r6
9+6r2-5+2r6=
4+6r2+2r6=
2(2+3r2+r6).
r= radical
(r3+r6)^2=
3+2r18+6=
9+6r2
(r2-r3)^2=
2-2r6+3=
5-2r6
9+6r2-5+2r6=
4+6r2+2r6=
2(2+3r2+r6).
r= radical
ctinamaria31xxx:
unde e gresit?
Răspuns de
0
=3+6+2rad18-2-3+2rad6=9+6rad2-5+2rad6=4+6rad2+2rad6
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Fizică,
10 ani în urmă
Matematică,
10 ani în urmă
Biologie,
10 ani în urmă
Matematică,
10 ani în urmă